New Random Fixed Point Results for Generalized Altering Distance Functions - Nashine, Hemant Kumar (Sarajevo Journal of Mathematics, 2024)
The aim of this work is to establish new random common fixed points for pair of mappings satisfying generalized weakly contractive conditions in the setting of complete metric spaces. 2000 Mathematics Subject Classification. 47H10, 54H25, 60H25